Extra Large G-Protein Interactome Reveals Multiple Stress Response Function and Partner-Dependent XLG Subcellular Localization - Liang, Ying; Gao, Yajun; Jones, Alan M. (Frontiers in Plant Science, 2017)
The three-member family of Arabidopsis extra-large G proteins (XLG1-3) defines the prototype of an atypical Gα subunit in the heterotrimeric G protein complex. Recent evidence indicate that XLG subunits operate along with its Gβγ dimer in root morphology, stress responsiveness and cytokinin induced development, however downstream targets of activated XLG proteins in the stress pathways are rarely known. To assemble a set of candidate XLG-targeted proteins, a yeast two-hybrid complementation-based screen was performed using XLG protein baits to query interactions between XLG and partner protein found in glucose-treated seedlings, roots, and Arabidopsis cells in culture. Seventy two interactors were identified and greater than 60% of a test set displayed in vivo interaction with XLG proteins. Gene co-expression analysis shows that greater than 70 % of the interactors are positively correlated with the corresponding XLG partners. Gene Ontology enrichment for all the candidates indicates stress responses and posits a molecular mechanism involving a specific set of transcription factor partners to XLG. Genes encoding two of these transcription factors, SZF1 and 2, require XLG proteins for full NaCl-induced expression. The subcellular localization of the XLG proteins in the nucleus, endosome, and plasma membrane is dependent on the specific interacting partner.